STRATEGI NABAWI DALAM MENDIDIK GENERASI: ANALISIS KUALITATIF TERHADAP KONSEP TADARRUJ DALAM HADIS BUKHARI - Mirhabun Nadir; Muhammad Ilmi Najib; Mahmudi, Rois; Damiri, Adam (IMTIYAZ: Jurnal Ilmu Keislaman, 2025)
This research aims to analyze in depth the educational strategy of the Prophet Muhammad SAW in the hadith narrated by Bukhari, with a focus on the pedagogical meaning of the concept of tadarruj or stages of imparting knowledge as contained in the words "Kuunuu Rabbaniyyin...". This research also explores the relevance of these principles in responding to the challenges of contemporary Islamic education, especially regarding the crisis in the character and spirituality of students. This research uses a qualitative approach with an interpretive case study type. Data collection techniques include in-depth interviews, observation and documentation carried out at the Darussalam Bayur Islamic Boarding School. Data were analyzed using the Miles and Huberman interactive model, and data validity was obtained through triangulation of sources and techniques. The research results show that the application of tadarruj principles in learning significantly helps in understanding the material, maintains the continuity of students' development, and makes it easier to identify their potential. This strategy has also proven effective in forming a complete and sustainable character. This research contributes to enriching the treasures of Islamic education by re-elevating the concept of Nabawi education as a contextual, solution and relevant approach to answering the problems of modern education based on spiritual and humanistic values.